The cognitive value of philosophical fiction - Mikkonen, Jukka (Bloomsbury studies in philosophy., 2013)
Can literary fictions convey significant philosophical views, understood in terms of propositional knowledge? This study addresses the philosophical value of literature by examining how literary works impart philosophy truth and knowledge and to what extent the works should be approached as communications of their authors. Beginning with theories of fiction, it examines the case against the prevailing 'pretence' and 'make-believe' theories of fiction hostile to propositional theories of literary truth. Tackling further arguments against the cognitive function and value of literature, this stud.